Point-of-care system for rapid real-time detection of SARS-CoV-2 virus based on commercially available Arduino platforms - Van Ngoc, Huynh; Quyen, Than Linh; Vinayaka, Aaydha Chidambara; Bang, Dang Duong; Wolff, Anders (Frontiers in Bioengineering and Biotechnology, 2022)
The COVID-19 pandemic has emphasised the importance of rapid, portable and on-site testing technologies necessary for resource-limited settings for effective testing and screening to reduce spreading of the infection. Realising this, we have developed a fluorescence based point-of-care detection system (fPOC) with real-time reverse transcriptase Loop-mediated Isothermal Amplification (rRT-LAMP) for rapid and quantitative detection of SARS-CoV-2 virus. The system is built based on Arduino platform compatible with commercially available open-source hardware-software and off-the-shelf electronic components. The fPOC system composes of three main components: 1) an instrument with integrated heaters, 2) optical detection components, and 3) an injection-molded polymeric cartridge. The system was tested and experimentally proved to be able to use for fast detection of SARS-CoV-2 virus in real-time in less than 30 min. Preliminary results of testing the performance of the fPOC revealed that the fPOC could detect SARS-CoV-2 virus at a limit of detection (LOD50%) at 2-3 copies/microlitre (15.36 copies/reaction) that was comparable to reactions run on a standard commercial thermocycler. The performance of the fPOC was evaluated with 12 SARS-CoV-2 clinical throat swab samples that included 7 positive and 5 negative samples as confirmed by RT-PCR. The fPOC showed 100% agreement with the commercial thermocycler. This simple design of the fPOC system has the potential to greatly enhance the practical applicability to develop total integrated point of care system for rapid on-site screening of SARS-CoV-2 virus in the pandemic management.